2008
DOI: 10.1590/s0100-204x2008000800012
|View full text |Cite
|
Sign up to set email alerts
|

Soybean cultivar BR-16-AHAS tolerance to the herbicide imazapyr

Abstract: -The objective of this work was to evaluate the effect of the transgenic soybean BR-16-AHAS genetic constitution on the tolerance to the herbicide imazapyr. BR-16-AHAS was crossed with ten other genotypes. The experimental design was a complete randomized block, in a 2x12x3 factorial arrangement, with two sowing periods (winter and summer), twelve crossing groups and three plant positions (upper, mid and lower), with three replicates. The plants were treated with 100 g ha -1 a.i. of imazapyr at the V3/V4 stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Similar results were reported by Okada et al (2002), who evaluated the offspring from crosses between transgenic (R 0 lines) and non transgenic sweet potato. Kiihl & Arias (2008) worked with a soybean line expressing the gene ahas, and also concluded that the resistance to imazapyr was inherited and adequately expressed in the ten genotypes recipients of the transgene.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported by Okada et al (2002), who evaluated the offspring from crosses between transgenic (R 0 lines) and non transgenic sweet potato. Kiihl & Arias (2008) worked with a soybean line expressing the gene ahas, and also concluded that the resistance to imazapyr was inherited and adequately expressed in the ten genotypes recipients of the transgene.…”
Section: Resultsmentioning
confidence: 99%